Daily Links Between Helping Behaviors and Emotional Well‐Being During Late Adolescence. (10th August 2020) - Armstrong‐Carter, Emma; Guassi Moreira, João F.; Ivory, Susannah L.; Telzer, Eva H.
Abstract : We investigated daily associations between helping behaviors and emotional well‐being during late adolescence, examining whether these links depend on the recipient of help (i.e., friend vs. roommate), type of help (i.e., instrumental vs. emotional), and individual differences in the helper (i.e., gender and empathy). First‐year college students ( N = 411, 63.5% women, M age = 18.62 years) completed diary checklists for eight days, reporting whether they provided instrumental and emotional support to a friend or roommate, and positive and negative emotions. On days that adolescents provided instrumental assistance to friends they felt more positive affect, but men also felt more negative affect. Providing instrumental and emotional support to roommates and providing emotional support to friends did not predict daily emotions.